2016
DOI: 10.1155/2016/2346025
|View full text |Cite
|
Sign up to set email alerts
|

A Water Hammer Protection Method for Mine Drainage System Based on Velocity Adjustment of Hydraulic Control Valve

Abstract: Water hammer analysis is a fundamental work of pipeline systems design process for water distribution networks. The main characteristics for mine drainage system are the limited space and high cost of equipment and pipeline changing. In order to solve the protection problem of valve-closing water hammer for mine drainage system, a water hammer protection method for mine drainage system based on velocity adjustment of HCV (Hydraulic Control Valve) is proposed in this paper. The mathematic model of water hammer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Limited space and the change of costly equipment are the main characteristics of mine drainage systems. For the problem of valve-closing water hammering, protection of a mine drainage system requires a protection method based on velocity adjustment of the hydraulic valve system [17]. Figure 18 shows the flow chart of the water hammering detection method.…”
Section: Comparison Of Previously Proposed Work With the Ml-based Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited space and the change of costly equipment are the main characteristics of mine drainage systems. For the problem of valve-closing water hammering, protection of a mine drainage system requires a protection method based on velocity adjustment of the hydraulic valve system [17]. Figure 18 shows the flow chart of the water hammering detection method.…”
Section: Comparison Of Previously Proposed Work With the Ml-based Workmentioning
confidence: 99%
“…Water hammering analysis is a vital work of a pipeline system's design process for water distribution networks. [17]. The most important results of a theoretical, experimental, and in situ investigation have been developed in connection with a water supply pumping pipeline failure.…”
Section: Introductionmentioning
confidence: 99%
“…Then Eqs. (17) and (18) can be solved using the characteristic line method [11]. It is noted that the cross-section areas of all the pipes are the same.…”
Section: Mathematic Model Of the Systemmentioning
confidence: 99%
“…Many scholars have studied this problem. Kou et al [11] proposed a method to reduce the water hammer based on multiple section velocity adjustments of the valve in a drainage system. Yao et al [12] pointed out that water hammer is due to the rapid opening and closing of the valve and proposed a scheme to delay the process, analysing the water hammer with the multi-scale asymptotic method.…”
mentioning
confidence: 99%
“…Apoloniusz Kondura [15] showed that the water hammer effect depends greatly on the characteristics of butterfly valve closure. Yanfei Kon et al [16] studied a water hammer protection method for mine drainage. They proposed a system that is based on adjusting the speed of the hydraulic control valve jumper.…”
Section: Introductionmentioning
confidence: 99%